A novel FSS for gain enhancement of printed antennas in UWB frequency spectrum. Issue 10 (October 2017) - Tahir, Farooq A.; Arshad, Talha; Ullah, Sadiq; Flint, James A.
Abstract: This paper presents a novel compact unilayer frequency selective surface (FSS) for ultra‐wideband (UWB) applications particularly for gain enhancement of printed antennas. The proposed FSS unit cell consists of simple metallic patterns printed on both sides of 14 mm × 14 mm FR4 substrate. The proposed FSS has very low transmission co‐efficient and linearly decreasing reflection phase over the bandwidth of 9 GHz in 3–12 GHz range, which makes it suitable candidate to provide in‐phase reflection for UWB antennas. For the validation of gain‐enhancement capability, the FSS is paired with a general monopole UWB antenna demonstrating an average gain improvement of 4 dB. The antenna composite has a maximum gain of 8.9 dBi.